Interrogating the Impact of Federalism on Clean Energy Transition: A Comparative Study of Nigeria, the United States of America, and Australia - Anifowose, Damilola Joseph; Ikubanni, Oluwaseye Oluwayomi (Journal of Sustainable Development Law and Policy, 2024)
The shift to clean energy sources from fossil fuels is critical and could be a challenge. However, this transition becomes even more complex in federal systems, where the interaction between the national and subnational governments creates unique challenges and also opportunities. This paper explored the dynamics of federalism in either facilitating or hindering the transition to clean energy. It focused on regulatory frameworks, policy approaches, and practical experiences in the USA and Australia. This paper also identified key challenges in this transition by looking at the case studies of the two countries. Additionally, this paper offered a comparative analysis with lessons and approaches that are particularly relevant to Nigeria and other federal nations, to achieve a sustainable clean energy transition. The research found that while federal structures present significant obstacles, they also provide opportunities for innovation and customized policy implementation toward a sustainable clean energy transition. Thus, the study recommended among others the need for a comprehensive national plan and advocates developing collaborative platforms for effective clean energy transition in Federal nations.